2011
DOI: 10.1055/s-0031-1300040
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Adjuvant Therapy in Rheumatoid Disease

Abstract: The aim of the present study was to assess the therapeutic value of adding a high dose of vitamin E or an antioxidant combination to the treatment regimen of the rheumatoid disease. The study was carried out on 30 patients with rheumatoid disease diagnosed according to the criteria of American Rheumatism Association (ARA), subvided into three equal groups. Patients in group I received a standard treatment of intramuscular methotrexate (CAS 59-05-2; 12.5 mg/week), oral sulphasalazine (CAS 599-79-1; 0.5 g b.i.d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
0
14
0
2
Order By: Relevance
“…In addition, a randomized controlled study had investigated the dietary intervention in patients with RA and it was observed that the levels of ascorbic acid, uric acid and retinol in human plasma were inversely correlated with rheumatoid biomarkers, hence suggesting possible dietary antioxidant interventions in RA management [20]. In another study, the co-administration of an antioxidant along with ordinary anti-rheumatic drugs for RA patients resulted in significant decrease in the plasma levels of RA biomarkers along with improved symptoms [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a randomized controlled study had investigated the dietary intervention in patients with RA and it was observed that the levels of ascorbic acid, uric acid and retinol in human plasma were inversely correlated with rheumatoid biomarkers, hence suggesting possible dietary antioxidant interventions in RA management [20]. In another study, the co-administration of an antioxidant along with ordinary anti-rheumatic drugs for RA patients resulted in significant decrease in the plasma levels of RA biomarkers along with improved symptoms [21].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the lengthening of life expectancy, our eating habits will be crucial in promoting human health. Further research should go in this direction in order to show new preventive and potential therapeutic strategies against several inflammatory chronic diseases [138]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have provided evidence that dietary supplementation with antioxidants may have beneficial effects on bony erosions in the management of some inflammatory arthritides, as well as osteoarthritis. [107][108][109][110][111][112][113][114][115][116][117][118][119][120] …”
Section: Free Radical Sequestering Of Antioxidantsmentioning
confidence: 99%